Hot-melt adhesive composition, pre-coating skin material for automotive interior, automotive interior material, and method for producing bonded body

By using the crystalline polyolefin, non -fixed polyolefin, and polypropylene waxes with a hardness of the Shaw's hardness of 80 or more, the existing hot -melt adhesive agent has poor operational performance when the mold is stripped. The problem of residue realizes the good adhesive and easy -to -peelbishness of the polyolefin substrate.

CN119384477APending Publication Date: 2025-01-28SUNSTAR GIKEN KK

Patent Information

Application Number
CN202380046702.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-29
Filing Date
2023-06-15
Publication Date
2025-01-28

Smart Images

  • Figure BDA0005184591400000251
    Figure BDA0005184591400000251
Patent Text Reader

Abstract

The present invention provides a hot melt adhesive comprising a crystalline polyolefin (A) having a Shore A hardness of 80 or more, an amorphous polyolefin (B), and a polypropylene wax (C), the amount of the polypropylene wax (C) being from 60 parts by weight to 300 parts by weight (inclusive) per 100 parts by weight of the total of the crystalline polyolefin (A) and the amorphous polyolefin (B). The hot-melt adhesive composition has good adhesion to a resin substrate, particularly to a polyolefin substrate such as polypropylene, and also has workability (mold releasability) that can be easily peeled off from a mold.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a hot melt adhesive composition, a pre-coated surface material for automobile interior using the hot melt adhesive composition, and an automobile interior material. Background Art

[0002] Hot melt adhesives are solid at room temperature, and are applied to substrates after being heated and melted, and then solidified by cooling to bond the substrates together. Compared with solvent-based adhesives, hot melt adhesives have advantages such as lower VOC and higher productivity due to the omission of drying steps, and can be used in various applications, such as automobile manufacturing.

[0003] Patent Document 1 discloses a hot-melt adhesive composition containing a hydrocarbon cyclic polymer, an α-olefin polymer, and a binder resin.

[0004] Patent Document 2 discloses a hot melt adhesive composition containing an α-olefin copolymer polymerized using a multi-site catalyst, an α-olefin copolymer polymerized using a single-site catalyst, an ethylene-polar group-containing monomer copolymer, a hydrogenated adhesive resin, and a polypropylene wax in a specific ratio.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: WO2018 / 012593

[0008] Patent Document 2: WO2018 / 100672 Summary of the invention

[0009] Technical problem to be solved by the invention

[0010] When using hot melt adhesives, depending on the type of bonding method, a process of peeling the hot melt adhesive from the mold is required (e.g., vacuum forming process). Patent Documents 1 and 2 do not study the process of peeling the hot melt adhesive from the mold. Conventional hot melt adhesives require time to solidify from a molten state, so they cannot be easily peeled from the mold during this period, resulting in poor workability. In addition, when conventional hot melt adhesives are used, the hot melt adhesive remains after being peeled from the mold, and it is necessary to peel or clean it manually, which is a problem from this aspect and from the perspective of workability.

[0011] Therefore, an object of the present disclosure is to provide a hot melt adhesive having good adhesion to a resin substrate, particularly a polyolefin substrate represented by polypropylene, and also having workability (mold releasability) that allows easy release from a mold.

[0012] Solutions to Solve Problems

[0013] That is, the present disclosure includes the following items:

[0014] [Item 1]

[0015] A hot-melt adhesive composition, comprising a crystalline polyolefin (A) having a Shore A hardness of 80 or more, an amorphous polyolefin (B) and a polypropylene wax (C), wherein the amount of the polypropylene wax (C) is 60 parts by weight or more and 300 parts by weight or less, based on 100 parts by weight of the total amount of the crystalline polyolefin (A) and the amorphous polyolefin (B).

[0016] [Item 2]

[0017] The hot-melt-adhesive composition according to item 1, wherein the melting point of the crystalline polyolefin (A) is 80° C. or higher.

[0018] [Item 3]

[0019] The hot-melt-adhesive composition according to item 1 or 2, wherein the crystalline polyolefin (A) comprises an ethylene-propylene copolymer.

[0020] [Item 4]

[0021] The hot-melt-adhesive composition according to any one of items 1 to 3, wherein the amorphous polyolefin (B) has a softening point of 100° C. or higher.

[0022] [Item 5]

[0023] The hot-melt adhesive composition according to any one of items 1 to 4, wherein the amorphous polyolefin (B) comprises at least one selected from the group consisting of binary copolymers of ethylene-propylene and ternary copolymers of ethylene-propylene-butene.

[0024] [Item 6]

[0025] The hot-melt-adhesive composition according to any one of items 1 to 5, wherein the softening point of the polypropylene wax (C) is 130° C. or higher.

[0026] [Item 7]

[0027] The hot-melt-adhesive composition according to any one of Items 1 to 6, comprising a binder (D).

[0028] [Item 8]

[0029] The hot-melt adhesive composition according to item 7, wherein the softening point of the adhesive (D) is 90° C. or higher.

[0030] [Item 9]

[0031] The hot-melt adhesive composition according to item 7, wherein the binder (D) comprises at least one selected from the group consisting of hydrogenated petroleum resins, terpene resins and terpene phenolic resins.

[0032] [Item 10]

[0033] The hot-melt-adhesive composition according to any one of Items 1 to 9, further comprising an antioxidant (E).

[0034] [Item 11]

[0035] The hot-melt-adhesive composition according to any one of Items 1 to 10, comprising an inorganic filler (F).

[0036] [Item 12]

[0037] The hot-melt adhesive composition according to any one of claims 1 to 11, comprising an elastomer (G).

[0038] [Item 13]

[0039] The hot-melt adhesive composition according to any one of items 1 to 12, wherein the melt viscosity at 180°C is 15,000 mPa·s or more and 100,000 mPa·s or less.

[0040] [Item 14]

[0041] The hot-melt adhesive composition according to any one of Items 1 to 13, which is used for an automobile interior material.

[0042] [Item 15]

[0043] A pre-coated surface material for automobile interior, comprising a surface material for automobile interior and a hot-melt adhesive layer formed from the hot-melt adhesive composition according to any one of items 1 to 14 on the back surface of the surface material for automobile interior.

[0044] [Item 16]

[0045] An automobile interior material, comprising an automobile interior molded article and the automobile interior pre-coat skin material according to item 15, wherein the automobile interior pre-coat skin material is bonded to the automobile interior molded article via the hot-melt adhesive layer.

[0046] [Item 17]

[0047] A method for manufacturing an adhesive body, wherein:

[0048] The adhesive body comprises a first substrate and a second substrate, wherein the second substrate is bonded to the first substrate via a hot-melt adhesive layer formed from the hot-melt adhesive composition according to any one of items 1 to 14.

[0049] The method for producing an adhesive body includes a step of bringing a mold into contact with the hot-melt adhesive composition.

[0050] Effects of the Invention

[0051] The hot melt adhesive disclosed in the present invention has good adhesion to polyolefin substrates represented by polypropylene, has good mold releasability, and is excellent in workability. DETAILED DESCRIPTION

[0052] <Hot-melt adhesive composition>

[0053] The hot melt adhesive composition of the present invention comprises a crystalline polyolefin (A), an amorphous polyolefin (B) and a polypropylene wax (C). In addition to (A) to (C), the hot melt adhesive composition of the present invention may further comprise one or more selected from a binder (D), an antioxidant (E), an inorganic filler (F), an elastomer (G), a plasticizer (H), other additives (I) and the like as needed.

[0054] [(A) Crystalline polyolefin]

[0055] The hot melt adhesive composition of the present disclosure comprises a crystalline polyolefin (A). Crystalline polyolefin (A) is a polyolefin with high crystallinity. From the viewpoints of crystallinity, Shore A hardness and / or molecular weight, crystalline polyolefin (A) is a substance different from other components described in this specification. Typically, the crystallinity of crystalline polyolefin (A) is 20% or more. Typically, the Shore A hardness of crystalline polyolefin (A) is 80 or more. Typically, the weight average molecular weight of crystalline polyolefin (A) is 40,000 or more.

[0056] The crystallinity of the crystalline polyolefin (A) may be 20% or more, 25% or more, 30% or more, or 35% or more. The crystallinity of the crystalline polyolefin (A) may be 100% or less, 98% or less, 95% or less, 90% or less, or 85% or less. From the viewpoint of better exerting the effect of the present disclosure, it is appropriate for the crystallinity to be above the above lower limit. The crystallinity can be measured, for example, by differential scanning calorimetry, X-ray diffraction of the polymer, etc. It should be noted that "crystallinity" in the present disclosure may refer to the property of observing a clear endothermic peak originating from the crystalline part in the differential scanning calorimetry, and on the other hand, "amorphous" may refer to the property of not observing a clear endothermic peak originating from the crystalline part in the differential scanning calorimetry.

[0057] The Shore A hardness of the crystalline polyolefin (A) may be 80 or more, 85 or more, 90 or more, or 95 or more, preferably 85 or more, and more preferably 90 or more. The Shore A hardness of the crystalline polyolefin (A) may be 100 or less, 99 or less, 98 or less, or 97 or less. The Shore A hardness may be used as an index of the cohesive force of the resin, and may be used as one of the indexes of room temperature adhesion and thermal adhesion. From the viewpoint of better exerting the effects of the present disclosure, it is appropriate for the Shore A hardness of the crystalline polyolefin (A) to be within the above range.

[0058] The melting point of the crystalline polyolefin (A) may be 60°C or higher, 70°C or higher, 80°C or higher, 90°C or higher, 100°C or higher, or 110°C or higher, and is preferably 80°C or higher. The melting point of the crystalline polyolefin (A) may be 150°C or lower, 140°C or lower, 130°C or lower, 120°C or lower, 110°C or lower, 100°C or lower, or 90°C or lower, and is preferably 120°C or lower, for example, 110°C or lower or 100°C or lower. From the viewpoint of better exerting the effects of the present disclosure, it is appropriate that the melting point of the crystalline polyolefin (A) is within the above range.

[0059] The glass transition temperature of the crystalline polyolefin (A) may be -150°C or higher, -125°C or higher, -100°C or higher, -75°C or higher, -50°C or higher, or -25°C or higher. The glass transition temperature of the crystalline polyolefin (A) may be 20°C or lower, 10°C or lower, 0°C or lower, -10°C or lower, or -20°C or lower, preferably 0°C or lower, and more preferably -10°C or lower. From the viewpoint of low-temperature adhesiveness, the glass transition temperature is preferably below the above upper limit.

[0060] Crystalline polyolefin (A) is typically thermoplastic. The MFR of crystalline polyolefin (A) can be 3g / 10 minutes or more, 5g / 10 minutes or more, 7g / 10 minutes or more, 10g / 10 minutes or more, 12g / 10 minutes or more, or 15g / 10 minutes or more, preferably 5g / 10 minutes or more, more preferably 7g / 10 minutes or more. The MFR of crystalline polyolefin (A) is 40g / 10 minutes or less, 30g / 10 minutes or less, 20g / 10 minutes or less, 15g / 10 minutes or less, or 10g / 10 minutes or less. From the viewpoint of low melt viscosity and coating stability, it is preferred that MFR is within the range above the above lower limit. MFR can be measured based on JIS K7210.

[0061] The weight average molecular weight of the crystalline polyolefin (A) may be 40,000 or more, 50,000 or more, 75,000 or more, 100,000 or more, 200,000 or more, 300,000 or more, or 500,000 or more, preferably 100,000 or more. The weight average molecular weight of the crystalline polyolefin (A) may be 5,000,000 or less, 2,000,000 or less, 1,500,000 or less, 1,200,000 or less, 1,000,000 or less, 800,000 or less, 600,000 or less, 400,000 or less, or 200,000 or less, preferably 1,000,000 or less, for example 600,000 or less. From the viewpoint of better exerting the effect of the present disclosure, it is appropriate that the weight average molecular weight is within the above range.

[0062] The crystalline polyolefin (A) is a polymer having repeating units derived from olefins. The crystalline polyolefin (A) is preferably an α-olefin polymer, particularly an α-olefin copolymer, having repeating units derived from α-olefins. The crystalline polyolefin (A) may be a homopolymer, a copolymer or a mixture thereof. The copolymer may be in the form of a random copolymer, a block copolymer, a graft copolymer or the like.

[0063] Examples of the repeating units contained in the crystalline polyolefin (A) include repeating units derived from ethylene, propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, 1-octadecene, 1-nonadecene, and 1-eicosene, and these repeating units may be contained alone or in combination of two or more thereof.

[0064] The crystalline polyolefin (A) preferably contains a repeating unit derived from propylene among the above repeating units, and for example, may contain both a repeating unit derived from propylene and a repeating unit derived from another α-olefin (e.g., ethylene). Among the repeating units constituting the crystalline polyolefin (A), the repeating unit derived from propylene may be 20 mol% or more, 30 mol% or more, 40 mol% or more, 50 mol% or more, 60 mol% or more, or 70 mol% or more, and preferably 30 mol% or more.

[0065] Specific examples of the crystalline polyolefin (A) include copolymers of olefins such as ethylene homopolymers, propylene homopolymers, ethylene-propylene copolymers, propylene-1-butene copolymers, ethylene-1-butene copolymers, ethylene-1-octene copolymers, ethylene-1-hexene copolymers, and ethylene-propylene-1-butene copolymers, and preferred examples include ethylene-propylene copolymers. These crystalline polyolefins (A) may be used alone or in combination of two or more.

[0066] Representative commercially available examples of the crystalline polyolefin (A) include TAFMER series products such as “TAFMER XM-7090”, “TAFMER XM-7080”, “TAFMER XM-7070”, “TAFMER XM-5090”, “TAFMER XM-5080”, “TAFMER XM-5070”, “TAFMER BL-2491M”, and “TAFMER DF110” manufactured by Mitsui Chemicals; VERSIFY series products such as “VERSIFY 3000” and “VERSIFY 4200” manufactured by Dow Chemical; Vistamaxx series products such as “Vistamaxx 8880”, “Vistamaxx 3000”, and “Vistamaxx 3980FL” manufactured by Exxon Mobil; and L-MODU S901, “L-MODU S600”, and “L-MODU S400” manufactured by Idemitsu Kosan Co., Ltd. In addition, the crystalline polyolefin (A) may be used alone or in combination of two or more.

[0067] [(B) Amorphous polyolefin]

[0068] The hot melt adhesive composition of the present disclosure comprises an amorphous polyolefin (B). An amorphous polyolefin (B) is a polyolefin that has no crystallinity or has a small amount of crystallinity and can impart flexibility. From the viewpoints of crystallinity and / or molecular weight, an amorphous polyolefin (B) is a substance that is different from other components described in this specification. Typically, the crystallinity of an amorphous polyolefin (B) is less than 20%. Typically, the weight average molecular weight of an amorphous polyolefin (B) is 40,000 or more.

[0069] The crystallinity of the amorphous polyolefin (B) may be 0% or more, 3% or more, or 5% or more. The crystallinity of the amorphous polyolefin (B) may be less than 20%, less than 15%, less than 10%, less than 5%, less than 3%, or less than 1%. From the viewpoint of better exerting the effect of the present disclosure, it is appropriate for the crystallinity to be less than the above upper limit. The crystallinity can be measured, for example, by differential scanning calorimetry, X-ray diffraction of the polymer, etc.

[0070] The softening point of the amorphous polyolefin (B) may be 70°C or more, 80°C or more, 90°C or more, 100°C or more, 110°C or more, 120°C or more, or 130°C or more, preferably 80°C or more, for example, 100°C or more. The softening point of the amorphous polyolefin (B) may be 180°C or less, 170°C or less, 160°C or less, 150°C or less, 140°C or less, 130°C or less, 120°C or less, or 110°C or less, preferably 160°C or less, for example, 140°C or less. From the viewpoint of better exerting the effects of the present disclosure, it is appropriate that the softening point of the amorphous polyolefin (B) is within the above range. The softening point can be measured by a ring and ball method.

[0071] The glass transition temperature of the amorphous polyolefin (B) may be -150°C or higher, -125°C or higher, -100°C or higher, -75°C or higher, -50°C or higher, or -25°C or higher. The glass transition temperature of the crystalline polyolefin (A) may be 20°C or lower, 10°C or lower, 0°C or lower, -10°C or lower, or -20°C or lower, preferably 0°C or lower, more preferably -10°C or lower. From the viewpoint of low-temperature adhesiveness, the glass transition temperature is preferably below the above upper limit.

[0072] Amorphous polyolefin (B) is typically thermoplastic. The MFR of amorphous polyolefin (B) can be 3g / 10 minutes or more, 5g / 10 minutes or more, 7g / 10 minutes or more, 10g / 10 minutes or more, 12g / 10 minutes or more, or 15g / 10 minutes or more, preferably 5g / 10 minutes or more, more preferably 7g / 10 minutes or more. The MFR of amorphous polyolefin (B) can be 40g / 10 minutes or less, 30g / 10 minutes or less, 20g / 10 minutes or less, 15g / 10 minutes or less, or 10g / 10 minutes or less. From the viewpoint of low melt viscosity and coating stability, it is preferred that MFR is within the range above the above lower limit. MFR can be measured based on JIS K7210.

[0073] The weight average molecular weight of the amorphous polyolefin (B) may be 40,000 or more, 50,000 or more, 75,000 or more, 100,000 or more, 200,000 or more, 300,000 or more, or 500,000 or more, preferably 100,000 or more. The amorphous polyolefin (B) may be 5,000,000 or less, 2,000,000 or less, 1,500,000 or less, 1,200,000 or less, 1,000,000 or less, 800,000 or less, 600,000 or less, 400,000 or less, or 200,000 or less, preferably 1,000,000 or less, for example, 600,000 or less. From the viewpoint of better exerting the effects of the present disclosure, it is appropriate that the weight average molecular weight is within the above range.

[0074] The amorphous polyolefin (B) is a polymer having repeating units derived from olefins. The amorphous polyolefin (B) is preferably an α-olefin polymer, particularly an α-olefin copolymer, having repeating units derived from α-olefins. The amorphous polyolefin (B) may be a homopolymer, a copolymer or a mixture thereof. The copolymer may be in the form of a random copolymer, a block copolymer, a graft copolymer or the like.

[0075] Examples of the repeating units contained in the amorphous polyolefin (B) include repeating units derived from ethylene, propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, 1-octadecene, 1-nonadecene, and 1-eicosene. These repeating units may be contained alone or in combination of two or more thereof.

[0076] The amorphous polyolefin (B) preferably contains repeating units derived from propylene among the above-mentioned repeating units, and for example, may contain both repeating units derived from propylene and repeating units derived from other α-olefins (e.g., ethylene). Among the repeating units constituting the amorphous polyolefin (B), the repeating units derived from propylene may account for 20 mol% or more, 30 mol% or more, 40 mol% or more, 50 mol% or more, 60 mol% or more, or 70 mol% or more, and preferably 30 mol% or more.

[0077] Specific examples of the amorphous polyolefin (B) include copolymers of olefins such as ethylene homopolymers, propylene homopolymers, ethylene-propylene copolymers, propylene-1-butene copolymers, ethylene-1-octene copolymers, ethylene-1-hexene copolymers, and ethylene-propylene-1-butene copolymers, and preferred examples include binary copolymers of ethylene-propylene and / or ternary copolymers of ethylene-propylene-butene. These amorphous polyolefins (B) may be used alone or in combination of two or more.

[0078] Typical commercially available examples of the amorphous polyolefin (B) include VESTOPLAST series products manufactured by Evonik under the trade names of “VESTOPLAST 308”, “VESTOPLAST 508”, “VESTOPLAST 520”, “VESTOPLAST 608”, “VESTOPLAST EP V2103”, “VESTOPLAST EP V2094”, “VESTOPLAST 708”, “VESTOPLAST 750”, “VESTOPLAST 751”, “VESTOPLAST 792”, “VESTOPLAST 828”, “VESTOPLAST 888”, “VESTOPLAST 891”, and “VESTOPLAST EP807”; and RT series products manufactured by REXtac under the trade names of “RT2280”, “RT2385”, “RT2585”, and “RT2780”.

[0079] [(C) Polypropylene wax]

[0080] The hot melt adhesive composition disclosed herein comprises a polypropylene wax (C). The polypropylene wax (C) refers to a wax having a repeating unit derived from propylene. The polypropylene wax (C) is usually low molecular weight (less than 40,000) and can impart coating properties and wettability to an adherend by reducing the viscosity of the hot melt adhesive. In addition, the polypropylene wax (C) can promote the crystallization and solidification of the crystalline polyolefin (A), increase the curing speed of the hot melt adhesive, and improve mold releasability.

[0081] The softening point of the polypropylene wax (C) is 90°C or more, 100°C or more, 110°C or more, 120°C or more, 130°C or more, 140°C or more, or 150°C or more, preferably 110°C or more, more preferably 120°C or more, and further preferably 130°C or more. The softening point of the polypropylene wax (C) may be 220°C or less, 210°C or less, 190°C or less, 180°C or less, 170°C or less, 160°C or less, or 150°C or less, preferably 190°C or less, for example, 160°C or less. From the viewpoint of better exerting the effects of the present disclosure, it is appropriate that the softening point of the polypropylene wax (C) is within the above range. The softening point of the polypropylene wax (C) can be measured by the ring and ball method. The softening point of the polypropylene wax (C) is below the above upper limit, and the melting temperature can be set lower, which is preferred from the viewpoint of shortening the working time.

[0082] The weight average molecular weight of the polypropylene wax (C) may be 3,000 or more, 5,000 or more, or 7,000 or more, preferably 3,000 or more. The weight average molecular weight of the polypropylene wax (C) may be less than 40,000, 35,000 or less, 30,000 or less, 20,000 or less, or 10,000 or less, preferably 20,000 or less. From the viewpoint of better exerting the effects of the present disclosure, it is appropriate that the weight average molecular weight is within the above range.

[0083] The polypropylene wax (C) may have repeating units other than repeating units derived from propylene, for example, repeating units derived from α-olefins. The polypropylene wax (C) may be a low molecular weight polyolefin, particularly a low molecular weight α-olefin polymer. The polypropylene wax (C) may be a homopolymer, a copolymer or a mixture thereof. The copolymer may be in the form of a random copolymer, a block copolymer, a graft copolymer or the like.

[0084] Examples of repeating units other than repeating units derived from propylene contained in the polypropylene wax (C) include repeating units derived from ethylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, 1-octadecene, 1-nonadecene, and 1-eicosene. These repeating units may be contained alone or in combination of two or more.

[0085] Among the repeating units constituting the polypropylene wax (C), the repeating units derived from propylene may account for 20 mol% or more, 30 mol% or more, 40 mol% or more, 50 mol% or more, 60 mol% or more, or 70 mol% or more, and preferably 30 mol% or more.

[0086] Representative commercial products of the polypropylene wax (C) include: VISCOL series products such as "VISCOL 660-P", "VISCOL 550-P", "VISCOL 440-P", and "VISCOL 330-P" manufactured by Sanyo Chemical Industries, Ltd.; HIWAX series products such as "HIWAX 100P", "HIWAX 200P", "HIWAX 400P", "HIWAX 800P", "HIWAX 410P", and "HIWAX 420P" manufactured by Mitsui Chemicals, Inc.; and Licocene series products such as "Licocene PP6102", "Licocene PP6502", and "Licocene PP7502" manufactured by Clariant Chemicals, Inc. It should be noted that the polypropylene wax (C) may be used alone or in combination of two or more thereof. Furthermore, waxes other than the polypropylene wax (C) may be blended within a range that does not impair the target physical properties.

[0087] [(D) Adhesive]

[0088] The hot melt adhesive composition of the present disclosure may contain a binder (D). The binder (D) can improve viscosity when melted.

[0089] The softening point of the adhesive (D) is 90°C or more, 100°C or more, 110°C or more, 120°C or more, 130°C or more, 140°C or more, or 150°C or more, preferably 110°C or more, more preferably 120°C or more, and further preferably 130°C or more. The softening point of the adhesive (D) may be 220°C or less, 210°C or less, 190°C or less, 180°C or less, 170°C or less, 160°C or less, or 150°C or less, preferably 190°C or less, for example, 160°C or less. From the viewpoint of better exerting the effects of the present disclosure, it is appropriate that the softening point of the adhesive (D) is within the above range. The softening point of the adhesive (D) can be measured by the ring and ball method. The softening point of the adhesive (D) is below the above upper limit, and the melting temperature can be set lower, which is preferred from the viewpoint of shortening the working time.

[0090] Examples of the binder (D) include rosin resin, rosin ester, disproportionated rosin ester, hydrogenated rosin ester, polymerized rosin, aliphatic hydrocarbon resin, aliphatic aromatic copolymer resin, aromatic petroleum resin, hydrogenated petroleum resin, terpene resin, hydrogenated terpene resin, modified terpene resin, hydrogenated modified terpene resin, terpene phenolic resin, hydrogenated terpene phenolic resin, styrene resin, coumarone resin, indene resin, etc. Among them, from the viewpoint of compatibility with polyolefin, preferred examples include hydrogenated petroleum resin, terpene resin or terpene phenolic resin. It should be noted that the binder (D) is a substance different from other components such as polyolefin from the viewpoint of the presence or absence of intramolecular double bonds, intramolecular polar groups, intramolecular hydrocarbon groups, etc.

[0091] Representative commercial products of the binder (D) include: ARKON series products manufactured by Arakawa Chemical Co., Ltd. under the trade names of “ARKON P-90”, “ARKON P-100”, “ARKON P-115”, “ARKON P-140”, “ARKON M-90”, “ARKON M-100”, “ARKON M-115”, and “ARKON M-135”; I MARV series products manufactured by Idemitsu Kosan Co., Ltd. under the trade names of “I MARVS-100”, “I MARV S-110”, “I MARV P-100”, “I MARV P-125”, and “I MARV P-140”; T-REZ series products manufactured by ENEOS under the trade names of “T-REZ HA125”, “T-REZ HB125”, and “T-REZ OP501”; and YS RESIN PX1250, “YS RESIN PX1150”, and “YS RESIN PX150” manufactured by Yasuhara Chemical Co., Ltd. YS RESIN series or YS POLYSTER series such as "YS RESIN PX1000", "YS RESIN PX1150N", "YS RESIN TO125", "YS RESIN TO115", "YS RESINTO105", "YS POLYSTER T160", "YS POLYSTER T145", "YS POLYSTER T130", "YS POLYSTER T115", "YS POLYSTER T100", and "YS POLYSTER UH115"; FTR series such as "FTR6100", "FTR6110", and "FTR6125" manufactured by Mitsui Chemicals, Inc., etc. It should be noted that the binder (D) may be used alone or in combination of two or more. Furthermore, a binder having a softening point of less than 90°C may be blended within a range that does not impair the target physical properties.

[0092] [(E) Antioxidant]

[0093] The hot melt adhesive composition of the present disclosure may contain an antioxidant (E). Inclusion of an antioxidant (E) is preferred from the viewpoint of improving thermal stability and exhibiting the effects of the present disclosure well.

[0094] Examples of the antioxidant (E) include hindered phenols, polyphenols, bisphenols, phosphoric acid esters, thioethers, hydrotalcites, benzimidazoles, and aromatic secondary amines.

[0095] Representative commercially available examples of the antioxidant (E) include: Irganox series products manufactured by BASF under the trade names of “Irganox 1010”, “Irganox 1035”, “Irganox 1076”, “Irganox 1098”, “Irganox 1330”, “Irganox 245”, “Irganox 259”, “Irganox 3114”, “Irganox 565”, and “Irgafos 168”; and ADEKA STAB AO-20, “ADEKA STAB AO-30”, “ADEKA STAB AO-40”, “ADEKA STAB AO-50”, “ADEKA STAB AO-60”, “ADEKA STAB AO-80”, “ADEKA STAB AO-330”, “ADEKA STAB PEP-8”, “ADEKA STAB PEP-36”, and “ADEKA STAB PEP-37” manufactured by ADEKA. HP-10", "ADEKASTAB 2112", "ADEKA STAB AO-412S" and other ADEKA STAB series, etc. In addition, the antioxidant (E) may be used alone or in combination of two or more.

[0096] [(F) Inorganic filler]

[0097] The hot melt adhesive composition of the present disclosure may contain an inorganic filler (F). By adding an inorganic filler (F), adhesiveness, sag properties, specific gravity, etc. can be adjusted.

[0098] Examples of the inorganic filler (F) include calcium carbonate (heavy calcium carbonate, surface untreated calcium carbonate, surface treated calcium carbonate (e.g., fatty acid treated calcium carbonate, etc.), needle-shaped crystalline calcium carbonate), silica (fumed silica, hydrophobic silica, precipitated silica, etc.), talc, mica (mica), clay, chrysotile, wollastonite, carbon black, graphite, balls (shirasu-balloons, glass balls, silica balls, etc.), inorganic fibers (glass fibers, metal fibers, etc.), titanium oxide, aluminum oxide, aluminum borate, silicon carbide, silicon nitride, potassium titanate, magnesium borate, titanium diboride, aluminum flakes, aluminum powder, iron powder, etc. It should be noted that the inorganic filler (F) may be used alone or in combination of two or more.

[0099] [(G) Elastomer]

[0100] The hot melt adhesive composition of the present disclosure may include elastomer (G). Elastomer (G) is a macromolecule showing elasticity. Elastomer (G) may be thermosetting or thermoplastic, preferably thermoplastic. From the viewpoints of crystallinity, Shore A hardness and / or molecular weight, elastomer (G) is a material that is different from other components described in this specification. Typically, elastomer (G) is not amorphous. Typically, the Shore A hardness of elastomer (G) is less than 80. Typically, the weight average molecular weight of elastomer (G) is more than 40,000.

[0101] The Shore A hardness of the elastomer (G) may be 20 or more, 30 or more, 40 or more, 50 or more, 60 or more, or 70 or more, and preferably 40 or more. The Shore A hardness of the elastomer (G) may be less than 80, less than 75, less than 70, less than 65, or less than 60. From the viewpoint of better exerting the effects of the present disclosure, it is suitable that the Shore A hardness of the elastomer (G) is within the above range.

[0102] The MFR of the elastomer (G) can be 3g / 10 minutes or more, 5g / 10 minutes or more, 7g / 10 minutes or more, 10g / 10 minutes or more, 12g / 10 minutes or more, or 15g / 10 minutes or more, preferably 5g / 10 minutes or more, and more preferably 7g / 10 minutes or more. The MFR of the elastomer (G) can be 40g / 10 minutes or less, 30g / 10 minutes or less, 20g / 10 minutes or less, 15g / 10 minutes or less, or 10g / 10 minutes or less. From the viewpoint of low melt viscosity and coating stability, it is preferred that the MFR is within the range above the above lower limit. The MFR can be measured based on JIS K7210.

[0103] The weight average molecular weight of the elastomer (G) may be 40,000 or more, 50,000 or more, 75,000 or more, 100,000 or more, 200,000 or more, 300,000 or more, or 500,000 or more, preferably 100,000 or more. The weight average molecular weight of the elastomer (G) may be 5,000,000 or less, 2,000,000 or less, 1,500,000 or less, 1,200,000 or less, 1,000,000 or less, 800,000 or less, 600,000 or less, 400,000 or less, or 200,000 or less, preferably 1,000,000 or less, for example, 600,000 or less. From the viewpoint of better exerting the effects of the present disclosure, it is appropriate that the weight average molecular weight is within the above range.

[0104] Examples of the elastomer (G) include rubber elastomers, olefin elastomers, styrene elastomers (e.g., hydrogenated or non-hydrogenated styrene elastomers), vinyl chloride elastomers, polyurethane elastomers, ester elastomers, and amide elastomers. Olefin elastomers are preferred from the viewpoint of compatibility. The olefin elastomer may be an olefin elastomer having a repeating unit derived from propylene.

[0105] Examples of representative commercial products of the elastomer (G) include TAFMER PN series such as "TAFMER PN-2070" and "TAFMER PN-3560" manufactured by Mitsui Chemicals, INFUSE series such as "INFUSE 9807", "INFUSE 9817" and "INFUSE 9990" manufactured by Dow Chemical, and Vistamaxx series such as "Vistamaxx 6502" and "Vistamaxx 6202" manufactured by Exxon Mobil. It should be noted that the elastomer (G) may be used alone or in combination of two or more.

[0106] [(H) Plasticizer]

[0107] The hot melt adhesive composition of the present disclosure may contain a plasticizer (H). The plasticizer (H) is an oily substance such as a low molecular weight compound containing a chain alkyl group or an olefin oligomer. The plasticizer (H) can improve the coating property and wettability to the adherend by reducing the viscosity of the hot melt adhesive.

[0108] The weight average molecular weight of the plasticizer (H) may be 100 or more, 300 or more, or 500 or more. The weight average molecular weight of the plasticizer (H) may be less than 3000, less than 2500, less than 2000, less than 1500, or less than 1000, preferably less than 2000. From the viewpoint of better exerting the effects of the present disclosure, it is appropriate that the weight average molecular weight is within the above range.

[0109] Examples of the plasticizer (H) include liquid paraffin, process oil, phthalic acid plasticizer, butene oligomer, butadiene oligomer, liquid ethylene-propylene oligomer, liquid rubber, etc. From the viewpoint of compatibility, butene oligomer or liquid ethylene-propylene oligomer is preferred.

[0110] Examples of representative commercial products of the plasticizer (H) include: POLYBUTENE series such as "POLYBUTENE 0N", "POLYBUTENE 015N", "POLYBUTENE 3N", "POLYBUTENE 10N", "POLYBUTENE 30N", and "POLYBUTENE 200N" manufactured by NOF Corporation; and LUCANT series such as "LUCANT LX004", "LUCANT LX010", "LUCANT LX020", "LUCANT LX100", "LUCANT LX200", "LUCANT LX400", and "LUCANT LX900Z" manufactured by Mitsui Chemicals, Inc. It should be noted that the plasticizer (H) may be used alone or in combination of two or more.

[0111] [(I) Other ingredients]

[0112] In addition to the above, the hot melt adhesive composition of the present invention may also contain other components (I) as needed. Examples of other components (I) include: colorants (e.g., red iron oxide (Bengala), titanium oxide, other coloring pigments, dyes, etc.); organic solvents (methanol, ethanol, isopropanol, butanol, acetone, methyl ethyl ketone, petroleum ether, ethyl acetate, tetrahydrofuran, n-hexane, heptane or isoparaffin high boiling point solvents, etc.); adhesives (silane coupling agents such as vinyltrimethoxysilane, vinyltriethoxysilane, aminosilane, mercaptosilane, epoxysilane, epoxy compounds such as glycidyl ether having a polyoxyalkylene skeleton, etc.); vulcanization accelerators (guanidines, aldehyde amines, aldehyde amines, thiazoles, sulfenamides, etc.). , thioureas, thiurams, dithiocarbamates, xanthates, etc.); vulcanization aids (long-chain fatty acids with more than 12 carbon atoms such as stearic acid, oleic acid, and palmitic acid; metal oxides such as zinc oxide, magnesium oxide, and lead oxide); antioxidants (hindered phenols, thiols, sulfides, dithiocarboxylates, thioureas, thiophosphates, thioaldehydes, etc.); ultraviolet absorbers and light stabilizers (benzotriazoles, hindered amines, etc.); thixotropic agents (colloidal silica, organic bentonite, fatty acid amides, hydrogenated castor oil, etc.); resins and polymer components other than the above (thermosetting resins, thermoplastic resins, etc.). These may be used alone or in combination of two or more.

[0113] The hot melt adhesive composition of the present disclosure may be a solvent-free type or may not contain a solvent.

[0114] The hot melt adhesive composition of the present disclosure may be non-reactive and may not contain reactive additives.

[0115] [composition]

[0116] The amount of the crystalline polyolefin (A) in the hot melt adhesive composition may be 2.5% by weight or more, 5% by weight or more, 7.5% by weight or more, 10% by weight or more, 12.5% ​​by weight or more, 15% by weight or more, 17.5% by weight or more, 20% by weight or more, 22.5% by weight or more, or 25% by weight or more, preferably 10% by weight or more, and more preferably 15% by weight or more. The amount of the crystalline polyolefin (A) in the hot melt adhesive composition may be 40% by weight or less, 35% by weight or less, 30% by weight or less, 25% by weight or less, 20% by weight or less, or 15% by weight or less, and preferably 30% by weight or less.

[0117] The amount of the amorphous polyolefin (B) in the hot melt adhesive composition may be 2.5% by weight or more, 5% by weight or more, 7.5% by weight or more, 10% by weight or more, 12.5% ​​by weight or more, 15% by weight or more, 17.5% by weight or more, 20% by weight or more, 22.5% by weight or more, or 25% by weight or more, preferably 10% by weight or more, and more preferably 15% by weight or more. The amount of the amorphous polyolefin (B) in the hot melt adhesive composition may be 40% by weight or less, 35% by weight or less, 30% by weight or less, 25% by weight or less, 20% by weight or less, or 15% by weight or less, and preferably 30% by weight or less.

[0118] The amount of the polypropylene wax (C) in the hot melt adhesive composition may be 10% by weight or more, 15% by weight or more, 20% by weight or more, 25% by weight or more, 30% by weight or more, 35% by weight or more, 40% by weight or more, 45% by weight or more, or 50% by weight or more, preferably 20% by weight or more, and more preferably 30% by weight or more. The amount of the polypropylene wax (C) in the hot melt adhesive composition may be 75% by weight or less, 70% by weight or less, 65% by weight or less, 60% by weight or less, 55% by weight or less, 50% by weight or less, or 45% by weight or less, preferably 65% ​​by weight or less, and more preferably 50% by weight or less.

[0119] The amount of the binder (D) in the hot melt adhesive composition may be 2.5% by weight or more, 5% by weight or more, 7.5% by weight or more, 10% by weight or more, 12.5% ​​by weight or more, 15% by weight or more, 17.5% by weight or more, 20% by weight or more, 22.5% by weight or more, or 25% by weight or more, preferably 10% by weight or more, and more preferably 15% by weight or more. The amount of the binder (D) in the hot melt adhesive composition may be 40% by weight or less, 35% by weight or less, 30% by weight or less, 25% by weight or less, 20% by weight or less, or 15% by weight or less, and preferably 30% by weight or less.

[0120] The amount of the antioxidant (E) in the hot melt adhesive composition may be 0.01% by weight or more, 0.05% by weight or more, 0.1% by weight or more, 0.3% by weight or more, 0.5% by weight or more, 0.75% by weight or more, or 1% by weight or more, preferably 0.1% by weight or more. The amount of the antioxidant (E) in the hot melt adhesive composition may be 5% by weight or less, 4% by weight or less, 3% by weight or less, 2% by weight or less, or 1% by weight or less, preferably 3% by weight or less.

[0121] The amount of the inorganic filler (F) in the hot melt adhesive composition may be 1% by weight or more, 2.5% by weight or more, 5% by weight or more, 7.5% by weight or more, 10% by weight or more, 12.5% ​​by weight or more, or 15% by weight or more, preferably 2.5% by weight or more, and more preferably 5% by weight or more. The amount of the inorganic filler (F) in the hot melt adhesive composition may be 30% by weight or less, 25% by weight or less, 20% by weight or less, 15% by weight or less, 10% by weight or less, or 5% by weight or less.

[0122] The amount of the elastomer (G) in the hot melt adhesive composition may be 0.5% by weight or more, 1% by weight or more, 2% by weight or more, 3% by weight or more, 4% by weight or more, 5% by weight or more, 6% by weight or more, 7% by weight or more, 8% by weight or more, 9% by weight or more, or 10% by weight or more, preferably 1% by weight or more, and more preferably 3% by weight or more. The amount of the elastomer (G) in the hot melt adhesive composition may be 25% by weight or less, 20% by weight or less, 15% by weight or less, 10% by weight or less, 7.5% by weight or less, 5% by weight or less, or 2.5% by weight or less, preferably 15% by weight or less, and more preferably 10% by weight or less.

[0123] The amount of other components (I) in the hot melt adhesive composition of the present disclosure can be appropriately selected according to each component. The total amount of other components (I) can be 0.1% by weight or more, 0.2% by weight or more, 0.5% by weight or more, 1% by weight or more, 2.5% by weight or more, or 5% by weight or more in the hot melt adhesive composition. The total amount of other components (I) can be 30% by weight or less, 25% by weight or less, 20% by weight or less, 15% by weight or less, 10% by weight or less, 7.5% by weight or less, or 5% by weight or less, 2.5% by weight or less, or 1% by weight or less in the hot melt adhesive composition, preferably 20% by weight or less, more preferably 10% by weight or less. The amount of each other component (I) can be 0.01% by weight or more, 0.05% by weight or more, 0.1% by weight or more, 0.3% by weight or more, 0.5% by weight or more, 0.75% by weight or more, 1% by weight or more, or 2.5% by weight or more in the hot melt adhesive composition. In addition, the amount of each of the other components (I) in the hot melt adhesive composition may be 10 wt% or less, 7.5 wt% or less, 5 wt% or less, 2.5 wt% or less, or 1 wt% or less. The amount of the plasticizer (H) may be based on the amount of the other components (I).

[0124] The total amount of crystalline polyolefin (A) and amorphous polyolefin (B) in the hot melt adhesive composition may be 5% by weight or more, 10% by weight or more, 15% by weight or more, 20% by weight or more, 25% by weight or more, 30% by weight or more, 35% by weight or more, 40% by weight or more, 45% by weight or more, or 50% by weight or more, preferably 20% by weight or more, and more preferably 30% by weight or more. The total amount of crystalline polyolefin (A) and amorphous polyolefin (B) in the hot melt adhesive composition may be 80% by weight or less, 70% by weight or less, 60% by weight or less, 50% by weight or less, 40% by weight or less, or 30% by weight or less, preferably 60% by weight or less. From the viewpoint of well exerting the effects of the present disclosure, it is appropriate that the total amount of crystalline polyolefin (A) and amorphous polyolefin (B) is within the above range.

[0125] Relative to 100 parts by weight of the amount of amorphous polyolefin (B), the amount of crystalline polyolefin (A) can be 15 parts by weight or more, 25 parts by weight or more, more than 50 parts by weight, 75 parts by weight or more, 100 parts by weight or more, 125 parts by weight or more, 150 parts by weight or more, preferably 25 parts by weight or more, more preferably 60 parts by weight or more, and more preferably 75 parts by weight or more. Relative to 100 parts by weight of the amount of amorphous polyolefin (B), the amount of crystalline polyolefin (A) can be 500 parts by weight or less, 450 parts by weight or less, 400 parts by weight or less, 350 parts by weight or less, 300 parts by weight or less, 200 parts by weight or less, 150 parts by weight or less, 100 parts by weight or less, 75 parts by weight or less, or 50 parts by weight or less, preferably 400 parts by weight or less, more preferably 300 parts by weight or less, and more preferably 200 parts by weight or less. From the viewpoint of well exerting the effect of the present disclosure, it is appropriate that the amount of crystalline polyolefin (A) is within the above range.

[0126] The amount of the polypropylene wax (C) may be more than 50 parts by weight, 60 parts by weight or more, 70 parts by weight or more, 80 parts by weight or more, 90 parts by weight or more, 100 parts by weight or more, 110 parts by weight or more, or 120 parts by weight or more, preferably 60 parts by weight or more, more preferably 80 parts by weight or more, and further preferably 90 parts by weight or more, relative to 100 parts by weight of the total amount of the crystalline polyolefin (A) and the amorphous polyolefin (B), The amount of the polypropylene wax (C) may be 350 parts by weight or less, 300 parts by weight or less, 250 parts by weight or less, 200 parts by weight or less, 150 parts by weight or less, or 100 parts by weight or less, preferably 300 parts by weight or less, more preferably 250 parts by weight or less, and further preferably 200 parts by weight or less. From the viewpoint of well exerting the effect of the present disclosure, the above range is preferred. When the content is above the lower limit, the crystallization promoting effect can be enhanced and mold releasability can be improved. When the content is below the upper limit, the adhesiveness can be enhanced.

[0127] Relative to the total amount of 100 parts by weight of crystalline polyolefin (A) and amorphous polyolefin (B), the amount of adhesive (D) can be 10 parts by weight or more, 20 parts by weight or more, 30 parts by weight or more, 40 parts by weight or more, 50 parts by weight or more, or 60 parts by weight or more, preferably 20 parts by weight or more, and more preferably 40 parts by weight or more. Relative to the total amount of 100 parts by weight of crystalline polyolefin (A) and amorphous polyolefin (B), the amount of adhesive (D) can be 150 parts by weight or less, 125 parts by weight or less, 100 parts by weight or less, 75 parts by weight or less, 50 parts by weight or less, or 30 parts by weight or less, preferably 100 parts by weight or less, and more preferably 75 parts by weight or less. From the viewpoint of well exerting the effect of the present disclosure, the above range is preferred.

[0128] Relative to the total amount of 100 parts by weight of crystalline polyolefin (A) and amorphous polyolefin (B), the amount of inorganic filler (F) can be 5 parts by weight or more, 10 parts by weight or more, 15 parts by weight or more, 20 parts by weight or more, 25 parts by weight or more, or 30 parts by weight or more, preferably 10 parts by weight or more, and more preferably 20 parts by weight or more. Relative to the total amount of 100 parts by weight of crystalline polyolefin (A) and amorphous polyolefin (B), the amount of inorganic filler (F) can be 75 parts by weight or less, 60 parts by weight or less, 50 parts by weight or less, 40 parts by weight or less, 30 parts by weight or less, or 20 parts by weight or less, preferably 60 parts by weight or less, and more preferably 40 parts by weight or less. From the viewpoint of well exerting the effect of the present disclosure, the above range is preferred.

[0129] Relative to 100 parts by weight of the total amount of crystalline polyolefin (A) and amorphous polyolefin (B), the amount of elastomer (G) can be 0.5 parts by weight or more, 1 part by weight or more, 3 parts by weight or more, 5 parts by weight or more, 7 parts by weight or more, 10 parts by weight or more, 12 parts by weight or more, or 15 parts by weight or more, preferably 3 parts by weight or more, and more preferably 10 parts by weight or more. Relative to 100 parts by weight of the total amount of crystalline polyolefin (A) and amorphous polyolefin (B), the amount of elastomer (G) can be 60 parts by weight or less, 50 parts by weight or less, 40 parts by weight or less, 30 parts by weight or less, 20 parts by weight or less, 15 parts by weight or less, or 10 parts by weight or less, preferably 40 parts by weight or less, and more preferably 20 parts by weight or less. From the viewpoint of well exerting the effect of the present disclosure, the above range is preferred.

[0130] [physical properties]

[0131] The hot melt adhesive composition disclosed herein has a melt viscosity of 5,000 mPa·s or more, 7,500 mPa·s or more, 10,000 mPa·s or more, 12,000 mPa·s or more, 15,000 mPa·s or more, 20,000 mPa·s or more, or 25,000 mPa·s or more, preferably 10,000 mPa·s or more, and more preferably 15,000 mPa·s or more, at 180° C., which is a normal coating temperature of the hot melt adhesive. The hot melt adhesive composition disclosed herein has a melt viscosity of 200,000 mPa·s or less, 150,000 mPa·s or less, 100,000 mPa·s or less, 50,000 mPa·s or less, 30,000 mPa·s or less, or 20,000 mPa·s or less at a normal application temperature of the hot melt adhesive, i.e., 180°C, preferably 150,000 mPa·s or less, and more preferably 100,000 mPa·s or less. If the melt viscosity is within the above range, no droplets or coating marks will be generated when applied to an adherend, so it is preferred. The above melt viscosity is a value measured using a parallel plate rheometer at a shear rate of 4.3 sec-1.

[0132] In the viscoelastic behavior of the hot melt adhesive composition of the present disclosure when it is rapidly cooled from 160°C at 33°C per minute, the storage elastic modulus at 60°C may be 1×10 4 Pa or more, 5×10 4 Pa or more, 1×10 5 Pa or above, 5×10 5 Pa or more, 1×10 6 Pa or above, 2×10 6 Pa or above or 3×10 6 Pa or more, preferably 1×10 5 Pa or more, more preferably 1×106 In the viscoelastic behavior of the hot melt adhesive composition of the present disclosure when it is rapidly cooled from 160°C to 33°C per minute, the storage elastic modulus at 60°C may be 1×10 8 Pa or less, 5×10 7 Pa or less, 1×10 7 Pa or less, 5×10 6 Pa or less, 3×10 6 Pa or less or 1×10 6 Pa or less. The storage elastic modulus is measured using a parallel plate rheometer at a shear rate of 4.3 sec -1 The value measured under the conditions of .

[0133] In the viscoelastic behavior of the hot melt adhesive composition of the present invention when being quenched from 160°C at 33°C per minute, the temperature at which tanδ reaches below 1 may be above 30°C, above 40°C, above 50°C, above 60°C or above 70°C, preferably above 40°C, and more preferably above 60°C. In the viscoelastic behavior of the hot melt adhesive composition of the present invention when being quenched from 60°C at 33°C per minute, the temperature at which tanδ reaches below 1 may be below 100°C, below 90°C, below 80°C or below 70°C, preferably below 80°C. It should be noted that tanδ is the loss tangent, and the ratio of the storage shear modulus (G') to the loss shear modulus (G") is G" / G'. tanδ is measured using a parallel plate rheometer at a shear rate of 4.3sec -1 The value measured under the conditions of .

[0134] <Method for producing hot-melt adhesive composition>

[0135] The hot melt adhesive composition of the present disclosure can be produced by mixing (A) to (C). For example, the hot melt adhesive composition can be produced by mixing (A) to (C) together with other components as needed using a heating mixer.

[0136] <Adhesive body and method for producing the same>

[0137] The adhesive body of the present disclosure includes a first substrate and a second substrate, and the second substrate is bonded to the first substrate via a hot-melt adhesive layer formed of a hot-melt adhesive composition.

[0138] The method for manufacturing an adhesive body disclosed in the present invention includes the following steps: applying the hot melt adhesive composition disclosed in the present invention on one surface of a first substrate to form a hot melt adhesive layer (coating step); and bonding the first substrate and the second substrate via the hot melt adhesive layer (bonding step). The method for manufacturing an adhesive body disclosed in the present invention may also include a curing step for crystallizing the hot melt adhesive layer.

[0139] [Base material]

[0140] There are no particular restrictions on the substrates used as the first substrate and the second substrate, and examples thereof include: wood materials; plastic materials such as polyolefins, polyvinyl chloride, polyurethane, polyester, epoxy resin, etc.; foams of the above plastic materials; rubber materials such as natural rubber and synthetic rubber; metal materials such as aluminum, iron, stainless steel, etc.; materials made of inorganic materials such as ceramics. There are no particular restrictions on the shape of each substrate, and for example, it can be a sheet, foil, plate, or molded body. In addition, each substrate can be composed of only one material or two or more materials. The material of the surface of the substrate provided with the adhesive layer is preferably non-metal, more preferably a resin as described above, and further preferably a polyolefin represented in particular by polypropylene.

[0141] [Coating process]

[0142] In the coating process, various hot melt adhesive coaters can be used as a method for coating the substrate, and methods such as using a spray gun, a comma coater, a die coater, and a roller coater can be cited. When coating the substrate, it can usually be heated at a temperature of 140°C to 200°C to melt it, and coated in a molten state. After coating on a release film or release paper, it can be thermally transferred to other substrates for use. By cooling after coating, the hot melt adhesive layer can be solidified on the substrate. The pre-coated substrate (substrate containing an adhesive layer) obtained after the coating process can be directly supplied to the next molding process, or it can be stored and then supplied to the next process.

[0143] [Bonding process]

[0144] In the bonding process, the hot melt adhesive layer can be heated and activated to melt again as needed. As a means of heating and activation, there are methods such as heating, ultrasonic waves, high frequency, microwaves, etc., which are not particularly limited. Reactivation is preferably carried out before the pre-coated substrate and the second substrate are crimped. The crimping of the pre-coated substrate and the second substrate is carried out before the hot melt adhesive composition layer is solidified. There is no particular limitation on the crimping method, and for example, crimping molding process, vacuum molding process, etc. can be cited. The second substrate may be heated or not. In addition, if the hot melt adhesive composition layer is in a reactivated state, it may not be heated during crimping, but it may also be heated while pressurizing as needed.

[0145] The temperature of the heating activation is preferably 100° C. to 200° C., for example, 100° C. to 180° C., and more preferably 120° C. to 160° C., based on the surface temperature of the hot-melt adhesive layer. The pressure during the pressure bonding involving the bonding of the first substrate and the second substrate can be 0.01 MPa to 0.5 MPa, preferably 0.01 MPa to 0.20 MPa, and more preferably 0.01 MPa to 0.10 MPa. The time during the pressure bonding can be, for example, 1 second to 300 seconds, preferably 1 second to 60 seconds, and more preferably 10 seconds to 30 seconds.

[0146] [Contact with mold, peeling process]

[0147] The method for manufacturing an adhesive body of the present disclosure preferably includes a step of contacting a mold with a hot melt adhesive composition. The hot melt adhesive composition of the present disclosure may be contacted with the mold in a coating step or a bonding step. For example, the method for manufacturing an adhesive body of the present disclosure can be applied to a vacuum forming process including a step of contacting a mold with a hot melt adhesive composition.

[0148] The material of the mold is not limited, and examples thereof include metal and ceramic. Metal (for example, various alloys such as aluminum, iron, and stainless steel) is preferred.

[0149] The method for producing an adhesive body of the present disclosure may further include a step of peeling the hot-melt adhesive layer formed of the hot-melt adhesive composition from the mold. The hot-melt adhesive layer may be peeled from the mold after cooling.

[0150] <Automobile interior material and its manufacturing method>

[0151] [Automotive interior materials]

[0152] The automobile interior material disclosed herein includes an automobile interior molded article and an automobile interior skin material (hereinafter also referred to as "skin material"), wherein the automobile interior skin material is bonded to the automobile interior molded article via a hot melt adhesive layer formed from the hot melt adhesive composition disclosed herein. The skin material may be a skin material derived from a skin material containing a hot melt adhesive layer (pre-coated skin material). Examples of automobile interior materials include door trims, instrument panels, ceiling materials, rear trays, pillars, and the like.

[0153] As for the material of the molded article for automobile interior, there is no particular limitation as long as it is a material used for automobile interior materials, and examples thereof include: wood materials such as paper and wood; plastic materials such as polyolefins (polypropylene, polyethylene, ethylene-propylene copolymers, etc.), polyvinyl chloride, polyurethane, polyester, epoxy resin, nylon, polyester, polycarbonate, polyurethane, acrylic, ABS, PCABS, etc.; rubber materials such as natural rubber and synthetic rubber; metal materials such as aluminum, iron, stainless steel, etc.; inorganic materials such as ceramics, etc. The molded article for automobile interior can be composed of only one material or two or more materials. The material of the surface of the molded article for automobile interior provided with the adhesive layer is preferably the above-mentioned non-metallic molded article material for automobile interior, more preferably the above-mentioned molded article material for automobile interior made of resin, and further preferably a polyolefin represented by polypropylene.

[0154] The skin material is not particularly limited as long as it is a material used for automobile interior materials, and examples thereof include: plastic sheets such as polyolefins, soft polyvinyl chloride, and polyurethane; foams of the above plastics; rubber sheets such as natural rubber and synthetic rubber; textile materials such as woven fabrics and non-woven fabrics; metal foils such as aluminum, etc. The skin material may consist of only one layer, or may include two or more layers of the same material or different materials. As a skin material comprising two or more layers, examples thereof include: a sheet formed by laminating one or more layers of the above plastic foam on one or more layers of the above plastic sheet, rubber sheet, textile material, metal foil, etc. As such a laminated sheet, examples thereof include: soft polyvinyl chloride with polyolefin foam, olefin thermoplastic elastomer with polyolefin foam, fabric with polyurethane foam, etc. The material of the surface of the skin material provided with an adhesive layer is preferably a non-metallic material of the above skin material, more preferably a resin material of the above skin material, and further preferably a polyolefin represented by polypropylene.

[0155] [Manufacturing method of automobile interior material]

[0156] In the manufacturing method of the automobile interior material disclosed in the present invention, in the manufacturing method of the above-mentioned adhesive body, the adhesive body can be an automobile interior material, the first substrate can be a skin material, and the second substrate can be a molded product for automobile interior. Conversely, the following situation can also be adopted: the adhesive body is an automobile interior material, the first substrate is a molded product for automobile interior, and the second substrate is a skin material.

[0157] An example of a method for manufacturing an automotive interior material may include the following steps: applying the hot melt adhesive composition of the present invention to the back side of a skin material (e.g., a foamed surface of the skin material) to obtain a skin material (pre-coated skin material) containing a hot melt adhesive layer; reactivating the obtained pre-coated skin material with a far-infrared heater, etc., and then crimping the skin material to a molded article for automotive interior via the hot melt adhesive layer after melting the hot melt adhesive layer. Furthermore, a curing step for crystallizing the hot melt adhesive layer may also be included. It should be noted that in the step of crimping with a substrate, when heating and crimping can be performed, it is sometimes not necessary to reactivate using a far-infrared heater, etc. It should be noted that the back side of the skin material refers to the side opposite to the molded article for automotive interior when the skin material is bonded to the molded article for automotive interior.

[0158] Example

[0159] Hereinafter, the present disclosure will be described in more detail with reference to Examples and Comparative Examples, but the present disclosure is not limited to these Examples and Comparative Examples.

[0160] <Examples 1 to 13 and Comparative Examples 1 to 5>

[0161] According to the composition shown in the following Table 1, each component shown below was mixed at 180° C. using a mixing stirrer (double-arm kneader SV-1-1 manufactured by Moriyama Seisakusho Co., Ltd.) to obtain a hot-melt adhesive composition.

[0162] Table 1

[0163]

[0164] [Ingredient A]

[0165] A-1: VERSIFY 4200 manufactured by Dow Chemical (melting point 84°C, Shore A hardness 94, propylene-ethylene copolymer)

[0166] A-2: VERSIFY 3000 manufactured by Dow Chemical (melting point 108°C, Shore A hardness 96, propylene-ethylene copolymer)

[0167] [Ingredient B]

[0168] B-1: VESTOPLAST 792 manufactured by Evonik (softening point 108°C, propylene, ethylene, butene copolymer)

[0169] · B-2: RT2585 manufactured by REXTAC (softening point 132°C, propylene-ethylene copolymer)

[0170] [Ingredient C]

[0171] C-1: VISCOL660-P manufactured by Sanyo Chemical Industries, Ltd. (softening point 145°C, weight average molecular weight 8000, polypropylene wax)

[0172] C-2: SANWAX171-P manufactured by Sanyo Chemical Industries, Ltd. (softening point 107°C, weight average molecular weight 9500, polyethylene wax)

[0173] [Ingredient D]

[0174] ·D-1: Arakawa Chemical Co., Ltd., ARKON P140 (softening point 140°C, hydrogenated petroleum)

[0175] ·D-2: Arakawa Chemical Co., Ltd., ARKON P90 (softening point 90°C, hydrogenated petroleum)

[0176] ·D-3: YS RESIN PN1150 manufactured by Yasuhara Chemical Co., Ltd. (softening point 115°C, terpene)

[0177] ·D-4: YS POLYSTER T145 manufactured by Yasuhara Chemical Co., Ltd. (softening point 145°C, terpene phenolic type)

[0178] [Ingredient E]

[0179] ·E-1: Irganox 1010 manufactured by BASF (melting point 110°C, hindered phenol)

[0180] E-2: Irgafos 168 manufactured by BASF (melting point 183°C, phosphorus type)

[0181] [Ingredient F]

[0182] ·F-1: Calcium carbonate 300 mesh manufactured by Shiraishi Calcium Co., Ltd.

[0183] [Ingredient G]

[0184] G-1: TAFMER PN-2070 manufactured by Mitsui Chemicals (melting point 140°C, Shore A hardness 75, propylene elastomer)

[0185] G-2: VISTAMAXX6202 manufactured by Exxon Mobil (Vicat softening point 48°C, Shore A hardness 61, propylene elastomer)

[0186] The hot melt adhesive compositions obtained in Examples 1 to 13 and Comparative Examples 1 to 4 were used to measure melt viscosity and cooling viscoelasticity as follows. Adhesion test specimens were prepared as follows and die releasability, initial creep, adhesive strength, and heat creep resistance were evaluated.

[0187] [Melt viscosity]

[0188] A parallel plate rheometer was used at a temperature of 180°C and a shear rate of 4.3 sec- 1 The results are shown in Table 1.

[0189] [Temperature at which the storage elastic modulus and tanδ become 1 or less during rapid cooling]

[0190] A parallel plate rheometer was used at a shear rate of 4.3 sec- 1 The viscoelastic behavior when quenched from 160°C at 33°C per minute was measured under the conditions of . The storage elastic modulus at 60°C was recorded. In addition, the temperature at which tanδ reaches or below 1 was recorded. The results are shown in Table 1. The temperature at which tanδ reaches or below 1 can be used as an indicator of mold releasability. In the initial stage of the measurement, since the hot melt adhesive is in a molten state, viscosity plays a dominant role compared to elasticity, so tanδ shows more than 1, but the hot melt adhesive is solidified by quenching, so elasticity plays a dominant role compared to viscosity. The temperature at which Tanδ reaches or below 1 can be considered as the temperature at which the hot melt adhesive solidifies.

[0191] [Preparation of Adhesion Test Sample 1]

[0192] The above adhesive was applied to the surface of the skin material (TPO / PPF, total thickness 4 mm) using a roll coater at 180°C so that the adhesive layer was 100 g / m2. Then, within 1 day after the adhesive was applied, the skin material was heated to 160°C or higher using a far-infrared heater, and immediately overlapped with an aluminum plate (thickness 1 mm), and pressed under 0.1 MPa for 15 seconds to obtain a laminate (adhesion test sample 1).

[0193] [Mold release properties]

[0194] Within one minute after obtaining the laminate (adhesion test sample 1), the peel strength (N / 25 mm) at 90 degrees peeling was measured using a push-pull gauge.

[0195] ○: 10N / 25mm or more

[0196] ×: less than 10N / 25mm

[0197] [Preparation of Adhesion Test Sample 2]

[0198] The above adhesive was applied to the surface of the skin material (TPO / PPF, total thickness 4 mm) using a roll coater at 180°C so that the adhesive layer was 100 g / m2. Then, within 1 day after the adhesive was applied, the skin material was heated to 160°C or higher using a far-infrared heater, and immediately overlapped with a PP plate (thickness 2 mm), and pressed under 0.1 MPa for 15 seconds to obtain a laminate (adhesion test sample 2).

[0199] [Initial creep]

[0200] After obtaining the laminate (adhesion test sample 2), a load of 200 g / 25 mm was applied in a 90-degree angle direction in an atmosphere at 60° C., and the peel length (mm) after 5 minutes was measured. The results are shown in Table 1.

[0201] BA: Interface failure on the substrate side

[0202] FB: Material failure of the surface material

[0203] CF: Cohesive failure of adhesive

[0204] The number after the damage state indicates the proportion of the damage state.

[0205] [Adhesion strength]

[0206] After curing the laminate (adhesion test sample 2) at 25°C for 24 hours, the peel strength (N / 25mm) at 180 degrees was measured. The PP plate was fixed with a clamp and the surface material was peeled off by stretching. The peeling speed was 200 mm / min. The results are shown in Table 1.

[0207] [Heat creep resistance]

[0208] After the laminate (adhesion test sample 2) was cured at 25°C for 24 hours, a load of 100 g / 25 mm or 200 g / 25 mm was applied at a 90-degree angle in an atmosphere at 80°C, and the peel length (mm) after 24 hours was measured. The results are shown in Table 1.

[0209] [result]

[0210] In the samples of Examples 1 to 13, good mold release and adhesive properties were obtained. In Comparative Examples 1 and 2, since the crystalline polyolefin (A) was not blended, the mold release and / or thermal creep resistance were reduced. In Comparative Examples 3 and 4, the blending amount of the polypropylene wax was outside the range of the present disclosure, so the mold release was reduced. In Comparative Example 5, since the polyethylene wax was used, the mold release and thermal creep resistance were reduced.

[0211] Industrial Applicability

[0212] The hot melt adhesive composition disclosed in the present invention can be used as a solvent-free adhesive without VOC emission, and has excellent adhesion and heat resistance to resin substrates, especially olefin substrates. In addition, since it can be easily peeled from the mold (for example, when bonding by vacuum forming process), it can be suitably used as an adhesive for automobile interior.

Claims

1. A hot melt adhesive composition, wherein: The invention comprises a crystalline polyolefin (A) having a Shore A hardness of 80 or more, an amorphous polyolefin (B) and a polypropylene wax (C), The amount of the polypropylene-based wax (C) is 60 parts by weight or more and 300 parts by weight or less relative to 100 parts by weight of the total amount of the crystalline polyolefin (A) and the amorphous polyolefin (B).

2. The hot-melt adhesive composition according to claim 1, wherein The melting point of the crystalline polyolefin (A) is 80° C. or higher.

3. The hot-melt adhesive composition according to claim 1 or 2, wherein The crystalline polyolefin (A) comprises an ethylene-propylene copolymer.

4. The hot-melt adhesive composition according to any one of claims 1 to 3, wherein The amorphous polyolefin (B) has a softening point of 100° C. or higher.

5. The hot-melt adhesive composition according to any one of claims 1 to 4, wherein The amorphous polyolefin (B) comprises at least one selected from the group consisting of a binary copolymer of ethylene-propylene and a ternary copolymer of ethylene-propylene-butene.

6. The hot-melt adhesive composition according to any one of claims 1 to 5, wherein The softening point of the polypropylene wax (C) is 130° C. or higher.

7. The hot-melt adhesive composition according to any one of claims 1 to 6, wherein Contains a binder (D).

8. The hot-melt adhesive composition according to claim 7, wherein The softening point of the binder (D) is 90° C. or higher.

9. The hot-melt adhesive composition according to claim 7 or 8, wherein The binder (D) comprises at least one selected from the group consisting of hydrogenated petroleum resins, terpene resins and terpene phenolic resins.

10. The hot-melt adhesive composition according to any one of claims 1 to 9, wherein Contains antioxidant (E).

11. The hot-melt adhesive composition according to any one of claims 1 to 10, wherein Contains an inorganic filler (F).

12. The hot-melt adhesive composition according to any one of claims 1 to 11, wherein Contains an elastomer (G).

13. The hot-melt adhesive composition according to any one of claims 1 to 12, wherein The melt viscosity at 180° C. is 15,000 mPa·s or more and 100,000 mPa·s or less. 14 . The hot-melt adhesive composition according to claim 1 , which is used for automobile interior materials.

15. A pre-coated surface material for automobile interior, wherein: The invention comprises a surface material for automobile interior and a hot-melt adhesive layer formed of the hot-melt adhesive composition according to any one of claims 1 to 14 on the back surface of the surface material for automobile interior.

16. An automobile interior material, wherein: The invention comprises a molded article for automobile interior and the pre-coat surface material for automobile interior according to claim 15, wherein the pre-coat surface material for automobile interior is bonded to the molded article for automobile via the hot-melt adhesive layer.

17. A method for producing an adhesive body, wherein: The adhesive body comprises a first substrate and a second substrate, wherein the second substrate is bonded to the first substrate via a hot-melt adhesive layer formed from the hot-melt adhesive composition according to any one of claims 1 to 14. The method for producing an adhesive body includes a step of bringing a mold into contact with the hot-melt adhesive composition.

Citation Information

Patent Citations

  • Hot-melt adhesive composition, method for using hot-melt adhesive composition, automobile interior material, precoated surface material for automobile interior, and method for producing automobile interior material

    WO2018100672A1

Cited By

  • PP / PA composite material for automobile front-end module and preparation method of PP / PA composite material

    CN121873475A